Content Validity of a New Soccer (Football) Return-to-Play Test: The RONDO-TEST - Sergi Matas; Carlos Lalín; Francisco Corbi; Antoni Planas-Anzano; José M. Moya; Sebastià Mas-Alòs; Xavier Peirau-Terés (Journal of Functional Morphology and Kinesiology)
Objectives: The aim was to assess the content validity of a new field test on general and soccer-specific motor skills before return to play. Methods: The RONDO-TEST was assessed by a Delphi panel for its content validity. It included a survey to evaluate 16 items related to the test consisting of four 10 m lines which cross over at their mid-point, resulting in eight 5 m sectors that include locomotor skills (speeding, moving sideways, side cutting, and jumping) and soccer-specific technical skills (dribbling, slalom course, and kicking/passing). The content validity was calculated with the Aiken’s V coefficient of acceptance at 0.69 and 95% of confidence interval. Results: Eight experts participated in the Delphi and agreed on the administration procedures after three rounds of suggestions. Major changes included the order of execution and the descriptions of the sectors. The results showed consensus (V = 1, maximum acceptance) for the clarity of instructions, the relevance of the skills to be evaluated, the order of execution, the materials and the relevance of measuring total and partial sector times. Conclusions: The RONDO-TEST may be feasible and simple to administer and evaluate technical functional skills (actions) and condition-related abilities (e.g., the ability to repeat the test, fatigue curve, etc.), which are relevant aspects for return to play under optimum conditions.